WTAP gene variants and susceptibility to ovarian endometriosis in a Chinese population - Wan, Zixian; Ye, Lu; Chen, Guange; Xiong, Chaoyi; OuYang, Zhenbo; Wu, Liangzhi; He, Jing; Duan, Ping; Jie, Youkun; Zhang, Qiushi; Hua, Wenfeng (Frontiers in Genetics, 2023)
Background: Endometriosis is a common chronic gynecologic disorder with a significant negative impact on women's health. Wilms tumor 1-associated protein (WTAP) is a vital component of the RNA methyltransferase complex for N 6 -methyladenosine modification and plays a critical role in various human diseases.However, whether single nucleotide polymorphisms (SNPs) of the WTAP gene predispose to endometriosis risk remains to be investigated.We genotyped three WTAP polymorphisms in 473 ovarian endometriosis patients and 459 control participants using the Agena Bioscience MassArray iPLEX platform. The logistic regression models were utilized to assess the associations between WTAP SNPs and the risk of ovarian endometriosis.Results: In the single-locus analyses, we found that the rs1853259 G variant genotypes significantly increased, while the rs7766006 T variant genotypes significantly decreased the association with ovarian endometriosis risk. Combined analysis indicated that individuals with two unfavorable genotypes showed significantly higher ovarian endometriosis risk (adjusted OR = 1.71[1.23-2.37], p = 0.001) than those with zero risk genotypes. In the stratified analysis, the risk effect of the rs1853259 AG/GG and rs7766006 GG genotypes was evident in subgroups of age ≤30, gravidity≤1, parity≤1, rASRM stage I, and the rs7766006 GG genotype was associated with worse risk (adjusted OR = 1.64[1.08-2.48] , p=0.021) in the patients with rASRM stage II+III+IV. The haplotype analysis indicated that individuals with GGG haplotypes had a higher risk of ovarian endometriosis than wild-type AGG haplotype carriers. Moreover, false positive report probability and Bayesian false discovery probability analysis validated the reliability of the significant results. The quantitative expression trait loci analysis revealed that rs1853259 and rs7766006 were correlated with the expression levels of WTAP.Our findings demonstrated that WTAP polymorphisms were associated with susceptibility to ovarian endometriosis among Chinese women.